Improved damage identification in bridge structures subject to moving loads: Numerical and experimental studies - Li, Jun; Law, S.; Hao, Hong (Pergamon, 2013)
This paper proposes a damage identification approach in bridge structures under moving vehicular loads without knowledge of the vehicle properties and the time-histories of moving interaction forces. The dynamic response reconstruction technique in wavelet domain is developed for a structure subject to moving vehicular loads. The transmissibility matrix between two sets of time-domain response vectors from the structure is formulated using the unit impulse response function in the wavelet domain with the moving loads at different locations. Measured acceleration responses of the structure in the damaged state are required for the identification, and the damage identification procedure is conducted without knowledge of the time-histories of the moving loads. A dynamic response sensitivity-based method is used for the structural damage identification, and local damage is modeled as a change in the elemental stiffness factors. The adaptive Tikhonov regularization technique is adopted to improve the identification results when noise effect is included in the measurements. Numerical studies on a three-dimensional box-section girder are conducted to illustrate the effectiveness and performance of the proposed approach, and the simulated damage can be effectively identified even with 10% noise in the measurements. The proposed method is also found capable to identify the damage zone with an approximate estimation of the damage extent when under the influence of initial model errors of the structure. Experimental studies on a Tee-section prestressed concrete beam subject to a moving vehicle are preformed to validate the proposed approach. Identification results from the experimental test data show that the damage locations can be identified with a reasonable estimate of the damage extent.